THE IMAGE OF NAVOI IN UZBEK POETRY (Scientific journal of the Fergana State University, 2023)
The article analyzes the poems that created the image of Navoi and reveals the peculiarities of the image. The lyrical interpretation of Navoi’s image is studied through Erkin Vohidov’s poem “Alisher Navoi’s ship” and Abdulla Sher’s poem “Missing Navoi”